Outcome of distal lower leg reconstruction with the propeller perforator flap in diabetic patients. Issue 4 (2nd August 2021) - Kim, Kyubeom; Kim, Junhyung; Jeong, Woonhyeok; Jo, Taehee; Park, Sang Woo; Choi, Jaehoon
Abstract: In diabetic foot patients, wound coverage options are quite limited due to vascular abnormalities. However, even though significant atherosclerotic changes are found in major vessels of the lower leg in diabetic foot patients, perforating vessels, which are used as the vascular pedicle of propeller perforator flaps, are often spared from atherosclerosis. Therefore, the propeller perforator flap could be an alternative option for diabetic foot patients. The purpose of this study was to compare the outcome of the propeller perforator flap between diabetic and nondiabetic patients in reconstruction of the distal lower leg. We retrospectively included all patients who underwent reconstruction of the distal lower leg with a propeller flap between 2014 and 2018. Thirty-five propeller perforator flaps in 20 diabetic patients and 15 nondiabetic patients were included. Of the 35 patients, 21 showed complete healing, and 14 showed flap complications. The rate of complications in diabetic patients was approximately 85.7%. Sex ( p = .002), diabetes ( p = .007), chronic renal failure ( p < .001), and diabetic neuropathy ( p = .011) were associated with flap complications. Crude regression analysis showed that the female sex ( p = .002), diabetes ( p = .01), and diabetic neuropathy ( p = .012) were significant risk factors for the occurrence of any complications, but the significance of diabetes and diabetic neuropathy was not maintained in the adjusted models. Therefore, the propeller perforator flap might not be effective for reconstructing diabetic foot ulcers.